Importance of Nitrogen and Zinc Fertility in Pecan Production - Niranjan Pokhrel; Louise Ferguson; Lu Zhang (Horticulturae)
Pecan is an important nut crop in the United States. It is native to North America and dominantly produced in the southern states in the US. Nitrogen and zinc are two of the most critical nutrients for pecan production. This review provides a comprehensive overview of nitrogen and zinc fertilizer management in pecan orchards, covering key topics such as nitrogen sources, nitrogen application rates, the timing of nitrogen application, nitrogen application of damaged trees, the impact of zinc deficiency, and methods for zinc application. The deficiency of these nutrients causes severe loss in pecan production. However, the cost involving nutrient application and post the effect of excessive application on the soil and environment is of serious discussion. This review summarizes nitrogen and zinc management strategy and explores application methods that can reduce the cost of fertilizer with minimal adverse effect on the soil and environment. Also, this review sheds light on the areas that needs extensive research in nutrient management in pecan production.